2011
DOI: 10.1007/s10517-011-1282-3
|View full text |Cite
|
Sign up to set email alerts
|

Monoaminergic Regulation of Hemopoiesis under Extreme Conditions

Abstract: The role of the adrenergic, dopaminergic, and serotoninergic systems in the regulation of hemopoiesis was evaluated on various models of pathological processes (restraint stress, experimental neurosis, and cytostatic treatment). The proliferation, differentiation, and maturation of polypotent, multipotent, partially determined, and oligopotent hemopoietic precursors and functional activity of microenvironmental cells (stromal cells, macrophages, and Thy1,2(+) cells) were shown to be under the control of a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Despite this, little work has been undertaken to examine the effects of glucocorticoid elevations on erythropoiesis. While many studies have reported hematopoietic and even myeloid responses to psychological stressors [18-24], very little work has been done to describe erythroid changes in response to chronic psychological stress. Previous work in our laboratory has demonstrated that prolonged RST elicits elevated stress responses for up to 28 days [32] and chief among these is a sustained elevation in circulating corticosterone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, little work has been undertaken to examine the effects of glucocorticoid elevations on erythropoiesis. While many studies have reported hematopoietic and even myeloid responses to psychological stressors [18-24], very little work has been done to describe erythroid changes in response to chronic psychological stress. Previous work in our laboratory has demonstrated that prolonged RST elicits elevated stress responses for up to 28 days [32] and chief among these is a sustained elevation in circulating corticosterone.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work demonstrates hematopoietic changes in rodents exposed to physical and psychosocial stressors [18-24]. However, the majority of reports focus on adrenergic and monoaminergic response and those specifically addressing myelopoiesis, finding diminished CFU-GM populations [19-22,24] without addressing the effects of psychological stress on erythroid development.…”
Section: Introductionmentioning
confidence: 99%
“…Hindlimb unloading induces changes of regional blood flow, particularly to the femur with its relatively limited blood supply , which could result in diminished erythropoiesis (Iversen et al, 1992). A putative central venous pressure increase in hindlimb-unloaded animals might diminish erythropoiesis (Montero et al, 2016), along with central mechanisms (Dygai and Skurikhin, 2011). Finally, hematopoietic stem cells seem to be inhibited by clinorotation (Plett et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Both circadian HSC trafficking and expression of CXCL12 are modulated by rhythmic release of sympathoadrenergic transmitters in the BM (Giudice et al, 2010 ). Several lines of evidence indeed suggest that hematopoiesis may be subject to catecholaminergic regulation even under extreme conditions, such as restraint stress and cytostatic treatment (Dygai and Skurikhin, 2011 ), although also the stress hormone corticosterone may exert major effects on HSC in the BM, as suggested by increased HSC apoptosis and reduced BM repopulation and stromal progenitor cell number following high corticosterone exposure and, on the other side, increased BM HSC and CXCL12 levels in animals with low corticosterone levels or treated with the corticosterone synthesis inhibitor metyrapone (Kollet et al, 2013 ). Indeed, transcriptome representation analyses showed relative expansion of the selective up-regulation of a subpopulation of immature proinflammatory monocytes (Ly-6c(high) in mice, CD16(-) in humans) within the circulating leukocyte pool in peripheral blood mononuclear cells from people subject to chronic social stress (low socioeconomic status) and mice subject to repeated social defeat (Powell et al, 2013 ).…”
Section: Effect Of Stress On the Production Of Inflammatory Cellsmentioning
confidence: 99%